THE RELATIONSHIP BETWEEN YODIUM AND ZINC INTAKE AND HEMOGLOBIN LEVELS IN ADOLESCENT WOMEN AT SMK PGRI 13 SURABAYA - Qotrunnada Munawaroh; Dini Setiarsih (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Lack of iodine and zinc intake in adolescents disrupted the metabolic process of iron in their bodies, leading to decreased hemoglobin levels in the blood and increasing the risk of anemia among adolescent girls. This study aimed to analyze the relationship between iodine and zinc intake and hemoglobin levels in adolescent girls at SMK PGRI 13 Surabaya. This research was a quantitative study with an analytic observational design. The research sample consisted of 104 respondents selected using Stratified Random Sampling. Data on iodine and zinc intake were collected using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and hemoglobin levels were measured digitally using the Point of Care Testing (POCT) method from capillary blood samples. Data analysis was performed using the Spearman Rank statistical test. The results showed that the average iodine intake was 63.68 mcg, and zinc intake was 4.24 mg, both classified as deficient. The average hemoglobin level was 12 g/dL. Spearman Rank test results indicated a significant relationship between iodine intake and hemoglobin levels (p-value = 0.032), and between zinc intake and hemoglobin levels (p-value = 0.030). The correlation coefficient values for iodine and zinc intake with hemoglobin levels were 0.210 and 0.213, respectively, indicating that the strength of the relationship between iodine and zinc intake and hemoglobin levels was weak.